Estrus synchronization and fixed time artificial insemination (AI) in pig: Improving the pig productivity - SINGH, MAHAK; Mollier, R Talimoa; Kumar, Rakesh; Katiyar, Rahul; Rajkhowa, D J; Mishra, V K (Indian Farming, 2022)
Estrus synchronization and fixed time artificial insemination in pig is a low cost second generation breeding technology which offers great advantages over conventional breeding. Besides improving pig productivity and efficiency, it also improves farm management. With this, pig germplasm of North East India can be improved in a shorter time interval. This technology is of much help to the farmers in remote areas where access to good breeding boar is a problem. This also significantly reduces the management cost and thereby improves the efficiency of the pigs. As there is no need to keep the boar for breeding thereby reduces the environmental footprints. Therefore, there is urgent need to percolate this technology to the farmers of this region.